2020
DOI: 10.1001/jamainternmed.2019.6544
|View full text |Cite
|
Sign up to set email alerts
|

Association of Default Electronic Medical Record Settings With Health Care Professional Patterns of Opioid Prescribing in Emergency Departments

Abstract: IMPORTANCE Prescription opioids play a significant role in the ongoing opioid crisis. Guidelines and physician education have had mixed success in curbing opioid prescriptions, highlighting the need for other tools that can change prescriber behavior, including nudges based in behavioral economics.OBJECTIVE To determine whether and to what extent changes in the default settings in the electronic medical record (EMR) are associated with opioid prescriptions for patients discharged from emergency departments (ED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
62
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 28 publications
4
62
0
Order By: Relevance
“…RenderX demonstrated that each tablet increase in preset yielded an increase of 0.19 tablets prescribed, and lower default quantities were associated with lower number of pills in 8 of 15 pairwise comparisons [25]. These results support our approach that modifications to prescription presets are an effective way to enact change in opioid prescribing.…”
Section: Xsl • Fosupporting
confidence: 70%
See 3 more Smart Citations
“…RenderX demonstrated that each tablet increase in preset yielded an increase of 0.19 tablets prescribed, and lower default quantities were associated with lower number of pills in 8 of 15 pairwise comparisons [25]. These results support our approach that modifications to prescription presets are an effective way to enact change in opioid prescribing.…”
Section: Xsl • Fosupporting
confidence: 70%
“…Despite a number of publications demonstrating reductions in opioid prescribing through presets [22,23,25], to our knowledge this research is the first to demonstrate reduction in overall opioid prescribing and prescribing of multiple individual opioids for an entire hospital system. Our hospitals and ambulatory clinics are located in one of the most lethal counties in one of the most lethal states associated with the opioid epidemic [38][39][40].…”
Section: Xsl • Fomentioning
confidence: 76%
See 2 more Smart Citations
“…In 10 recent studies, implementing a new or lower default dispense quantity for opioid analgesics, either alone or as part of a package of interventions, was associated with reductions in the quantity of new prescriptions. 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 In 2 studies, removing defaults, and therefore requiring prescribers to make an active choice with each prescription, yielded mixed results. 23 , 25 …”
Section: Introductionmentioning
confidence: 99%